Design and Determination of Strength of Adhesive Bonded Joints - Kalina, Tomáš; Sedláček, František (Manufacturing Technology Journal, 2019)
The paper deals with methodology of prediction of adhesive bonded joints strength. Problematics of adhesive bonded joints is a very complex task. There are several different (different precision and different complexity) mathematical models of adhesive bonded joints, which attempts to describe the real behavior of adhesive and adhesive bonded joints during load as accurately as possible. This article presents a comprehensive overview of what to take into account and how to proceed with designing/controlling the strength of adhesive bonded joints. Mathematical models are supplemented by material data from experimental tests. The proposed methodology takes into account both adhesive and cohesive properties (material of bonded parts, surface treatment of bonded material, type of adhesive, thickness of adhesive, bonding technology, loading modes etc.). Methodology "how to proceed" is described in detail and is complemented with a flowchart.
Keywords: Adhesive Bond; Cohesive parameters; Epoxy Adhesive; Methodology; Surface treatment